"Four Faces on One Neck": The Tetracephalic Ram as an Iconographic Form in the Late New Kingdom - Treasure, Matthew (AUC Knowledge Fountain, 2021)
In ancient Egypt, the ram was regarded as a symbol of protection, male virility, fertility, syncretism, rebirth, and resurrection, and the Egyptians accordingly associated some of their gods with the ram because of what it represented. The most popular ram deities, each connected with his own temples and cult centers at different geographic locations, were Banebdjed of Mendes, Heryshef of Herakleopolis Magna, Amun-Ra of Thebes, and Khnum of Esna and Elephantine. Similarly, numbers were another important aspect of Egyptian religion and magic, and the symbolic language of numbers manifested itself in a variety of ways in the art of ancient Egypt; occasionally, ram gods, for example, were represented with multiple heads in order to indicate the syncretism of two or, more frequently, four different divinities. This thesis engages with New Kingdom representations of four-headed ram deities, appearing in separate entrance scenes preserved inside the individual tombs of Ramesses IX (KV 6), Ramesses X (KV 19), and Ramesses XI (KV 4), as an artistic response to theological and political change in the late Twentieth Dynasty. This examination of art applies iconographic and iconological analysis on selected images of tetracephalic ram deities in order to better understand the symbolic message articulated by four rams’ heads as an iconographic form. Ultimately, the four-headed ram as an iconographic type during the late New Kingdom was applied to both solar and netherworld divinities, constituting a demiurge par excellence. Four rams’ heads, as a composite motif, also shows us that Egyptians of the late New Kingdom perceived many similarities between their individual ram gods, in particular, Banebdjed of Mendes and Amun-Ra of Thebes, who were each depicted in art by the Ramesside period occasionally as a tetracephalic ram deity.